2010
DOI: 10.1111/j.1365-2222.2010.03601.x
|View full text |Cite
|
Sign up to set email alerts
|

Production of interleukin‐5, ‐10 and interferon‐γ in cord blood is strongly associated with the season of birth

Abstract: Environmental exposure to pollen and ultraviolet irradiation during gestation may have an effect on the cytokine profile of the offspring in CB because children born in the spring or winter showed the lowest IL-5, IL-10 and IFN-γ responses. The production of IL-10 and IFN-γ was also inversely associated with prostaglandin labour induction before birth. Other labour-related factors were not significantly associated with production of IL-5, IL-10 and IFN-γ after WBC count correction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…Lundholm et al [105] demonstrated that increasing birth weight is a risk factor for AD, but not AR, clearly independent of gestational age, shared environmental and genetic factors. This indicates that fetal growth affects the immune system and points to early mechanisms in line with evidence from many birth cohort studies [79, 106–111]. Thomsen et al [112] confirmed the strong genetic component of asthma in children and adults, and that this may not extend to older adults.…”
Section: Epidemiology Of Allergic Diseasessupporting
confidence: 64%
See 1 more Smart Citation
“…Lundholm et al [105] demonstrated that increasing birth weight is a risk factor for AD, but not AR, clearly independent of gestational age, shared environmental and genetic factors. This indicates that fetal growth affects the immune system and points to early mechanisms in line with evidence from many birth cohort studies [79, 106–111]. Thomsen et al [112] confirmed the strong genetic component of asthma in children and adults, and that this may not extend to older adults.…”
Section: Epidemiology Of Allergic Diseasessupporting
confidence: 64%
“…Indeed, in frame of the LINA (Lifestyle and environmental Factors and their influence on Newborns Allergy risk) study, reduced frequencies of Treg cells together with Th2 cytokines IL‐4 and IL‐5 levels in blood collected at the 34th week of gestation correlated with increased IgE levels in cord blood [50]. Other immune determinants than maternal factors are, however, involved in cord blood: the stronger predictor of IL‐5, IL‐10 and IFN‐γ production in cord blood is the season of birth, with a higher level of cytokine production in spring vs. fall [79]. Still in cord blood, some mediators such as selected chemokines could serve as biomarkers predictive of atopic diseases.…”
Section: Mechanisms In Allergic Diseasementioning
confidence: 99%
“…The PCA is described in details in the Supplemental Digital Content 1, http://links.lww.com/INF/C406. All associations were adjusted for gender [21][22][23] and season of birth. [23][24][25] All statistical analysis are based on a linear quasipoison regression, while in the graphical presentation of the results, the children are partitioned into 3 groups based on the number of LRI.…”
Section: Methodsmentioning
confidence: 99%
“…The season in which a person is born influences their risk of allergic disease: those born in autumn and winter typically have higher risks of developing many allergic diseases including food allergy. This is also manifested at the immunological level, as exemplified by season of birth being the strongest predictor of cytokine production in cord blood cells . The primary stimuli underlying the season of birth effect on allergic disease are unknown, but may include ultraviolet light/vitamin D levels, pollen and viral infection timing, and seasonal variations in nutrition.…”
Section: In Utero Exposures That Influence Allergymentioning
confidence: 99%